EFEKTIFITAS PENDIDIKAN KESEHATAN DENGAN AUDIO VISUAL TERHADAP PENGETAHUAN DAN PERILAKU HIDUP SEHAT KELUARGA TENTANG PENCEGAHAN PENULARAN TUBERKULOSIS PARU - Muhammad Syarif Buang; Siti ' Rahmalia; Arneliwati ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
The purpose of this research was to determine the effectiveness of health education by using audio visual media for knowledge and healthy life behavior to prevent spreading lung tuberculosis. The design of this research was quasy experiment by applicatied of health education through audio-visual media. The research was conducted in Puskesmas Harapan Raya Pekanbaru with 30 respondens who are taken by used purposive sampling technique. The data was colected by used a questionnaire that had been tested for validity (0,482 – 0,959 and 0.484 – 0.834) and reliability (0,906 and 0.909). Data colected was analysis by univariate and bivariate using dependent t test and independent t test. The results showed that there was very significan the health education to prevent spreading by audio visual to increase knowledge and healthy life behaviour in the experimental group after the health education given with p value (0,000). According the result of research, health provider need provide regulerly health education by audio visual to prevent and enchance knowledge of people who has diagnose tuberculosis.   Keyword : audio visual, health education, healthy life behaviour, Knowledge,  lung tuberculosis.